ChemInform Abstract: A Thioannulation Approach to Substituted Thiophenes from Morita—Baylis—Hillman Acetates of Acetylenic Aldehydes. Issue 48 (26th November 2013) - Reddy, Chada Raji; Valleti, Redi Rani; Reddy, Motatipally Damoder
Abstract The new and versatile protocol for the title approach proceeds under mild and metal‐free reaction conditions and through a tandem allylic substitution/deacetylative thiocycloisomerization.